2022
DOI: 10.1002/wcc.806
|View full text |Cite
|
Sign up to set email alerts
|

Computational methods for the analysis of climate change communication: Towards an integrative and reflexive approach

Abstract: Computational methods, in particular text‐as‐data or Natural Language Processing (NLP) approaches, have become popular to study climate change communication as a global and large‐scale phenomenon. Scholars have discussed opportunities and challenges of these methods for climate change communication, with some proponents and critics taking strong positions, either embracing the potential of computational methods or critically questioning their value. Mirroring developments in the broader social scientific debat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…As Lauer et al (2018) suggested, sometimes AI tools are treated as black boxes. We also share the concerns raised by Schäfer and Hase (2023) that computational methods, if used uncritically, risk reintroducing empiricist epistemologies that trade human researcher bias for precise measurements of the wrong constructs or for data-driven bias. In this case, the black box of AI would be used to launder uncritical and unrigorous work, ultimately leading to invalid results.…”
Section: Construct Validity Tpc and Aimentioning
confidence: 89%
See 1 more Smart Citation
“…As Lauer et al (2018) suggested, sometimes AI tools are treated as black boxes. We also share the concerns raised by Schäfer and Hase (2023) that computational methods, if used uncritically, risk reintroducing empiricist epistemologies that trade human researcher bias for precise measurements of the wrong constructs or for data-driven bias. In this case, the black box of AI would be used to launder uncritical and unrigorous work, ultimately leading to invalid results.…”
Section: Construct Validity Tpc and Aimentioning
confidence: 89%
“…Such a focus enables graduate students to assess the affordances and trade-offs of choosing particular methods, especially computationally based ones. Adding construct validity to graduate training, then, can direct the field in the reflexive and integrative direction between a rejection of computational methods and an uncritical acceptance of them (Schäfer & Hase, 2023).…”
Section: Construct Validity and Graduate Research Preparationmentioning
confidence: 99%
“…The above-mentioned findings could help in designing effective climate change communication strategies (e.g., [152][153][154][155][156]). If creative and happy individuals are indeed more concerned about climate change, then tailored messaging and campaigns could be developed, leveraging emotional and creative inclinations as well as encouraging participation in significant sustainability projects, programs, and other activities, including sustainability communication within the frame of citizen science [157]. The findings of this study might also have implications for policy development; if creative and happy individuals are more concerned about climate change, policymakers could consider their perspectives when crafting climate policies, potentially leading to more effective and widely accepted solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Public awareness of the greenhouse effect has increased steadily since the mid-1980s (Nisbet and Myers 2007). Many different aspects of anthropogenic climate change have featured in the news media and innovative ways of analyzing the growing corpus of media coverage are being applied (Hase et al 2021;Schäfer and Hase 2023). Regarding climate tipping points, the media coverage has steeply increased since about 2017, when also digital news media showed an accelerating mention of this and related terms (Bellamy 2023).…”
Section: Consensus Finding Process Promotes Scientific Progressmentioning
confidence: 99%